Informed indulgence: the effects of nutrition information provision and dietary restraint on consecutive food consumption decisions. Issue 11 (2nd November 2021) - Oh, Ga-Eun (Grace); Huh, Young Eun; Mukhopadhyay, Anirban
Abstract: Objective: Nutrition and menu labelling have been increasingly implemented worldwide. This research examines the effect of nutrition information provision on the immediate and subsequent consumption decisions of restrained and unrestrained eaters. Design: We conducted three scenario-based experiments. In Study 1 ( N = 478) and Study 2 ( N = 199), we manipulated the availability of nutrition information and measured dietary restraint. Study 3 ( N = 275) extended Study 2 by adding a condition where we provided reference information about recommended daily calories. Main outcome measures: We measured choices between relatively low-calorie and high-calorie alternatives (Studies 1–3) and measured a subsequent decision to consume indulgent food (Studies 2 and 3). Results: Nutrition information did not generally affect choices between low-calorie and high-calorie options, irrespective of dietary restraint. However, restrained eaters who chose a high-calorie option in the presence of nutrition information indicated they would reduce subsequent intake. Conclusion: Nutrition information does not necessarily reduce the choice of relatively high-calorie food, but it can help restrained eaters reduce subsequent intake after a high-calorie choice. These results suggest that despite not having an immediate effect on choices, nutrition and menu labelling may benefit restrained eaters at a later time.